The Influence of Capital Structure and Asset Efficiency on Profitability and Corporate Income Tax - Kurniawan, Andrie; Putra, Dian Berliansyah; Sofyanty, Devy; Aryadi, Heri (Jurnal Multidisiplin Sahombu, 2025)
This study investigates the influence of asset efficiency and capital structure on profitability and corporate income tax in primary consumer goods sector companies listed on the Indonesia Stock Exchange for the 2020–2024 period. Using purposive sampling, 25 companies were selected, and data from audited financial statements were analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS. Asset efficiency, measured by Fixed Asset Turnover (FATO), shows no significant effect on profitability or corporate income tax, indicating that asset utilization alone is insufficient to enhance financial outcomes. Capital structure, proxied by the Debt-to-Equity Ratio (DER), significantly reduces profitability but does not significantly influence corporate income tax. Profitability has a positive and significant effect on corporate income tax, aligning with the Trade-Off Theory. These findings highlight the need for optimal leverage management, operational improvements beyond asset utilization, and effective tax strategies to ensure sustainable corporate performance.